Internet of Things For Surgery Process Using Raspberry Pi - Yanni, Rafeek Mamdouh Tawfiq; El-Bakry, Hazem M.; Riad, Alaa; El-Khamisy, Nashaat (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The development of the internet of things makes all objects interconnected, making it the next technical revolution. It has been applied extensively in various sectors, including agriculture, smart parking, and industrial places, and most importantly, in the health monitoring process.[1] To monitor or its application in surgery procedure is one of its uses in healthcare. This project proposes a system aimed to solve sudden occurrences and emergencies during the operation process. The system’s objective is to minimize deaths and other possible effects of the phenomena by connecting the surgeon with an online specialist all over the world. The proposed system architecture is based on medical sensors measuring the patient’s physical parameters utilizing wireless sensor networks. The sensors send the parameters to the Raspberry Pi, which converts them to digital data. The digital data is transferred over the wireless network to the server, which is then sent to the cloud environment using the internet of things. Additionally, In case of any problem, the system works by sending the surgeon a voice signal to open the system and record the message and send it with the video that was recorded by the Raspberry pi cameras through the server to all the surgeons involved in the system through the Internet of things all over the world. Then the surgeons from across the globe communicate according to his specialty of assistant surgeon to communicate with the surgeon inside the operating room through headset and microphone.